Perbedaan Lebar Lengkung Gigi pada Maloklusi Klasifikasi Angle di SMPNI Salatiga Jawa Tengah - Bakri, Fadel Firdaus, Dwi Kurniawati, S.KG, MPH, drg. Suyadi (2015)
Background: Dental arch could influence several factors concerned to such as available space, aesthetic, and teeth stability. Some researchers claimed that there was differences of dental arch width on malocclusion Angle classification while some others said the opposite. By knowing dental arch width, it can help practitioners in orthodontics, prosthodontics, and anthropology to understand the dimension of dental arch. Purpose : The purpose of this research is to know the difference of dental arch width on different malocclusion Angle classification at SMPN 1 Salatiga, Central Java. Method: This was analytical observational study with cross sectional survey design. 51 samples were choosen by purposive sampling method, with determined criteria as has to have complete permanent teeth from right first molar to left first molar. Dental arch width measurement was done at particular point, there were intercanine, first interpremolar, second interpremolar, first intermolar, first intermolar second point, both maxillary and mandibular. One way Anova test was applied to understand the differences between classes. Result: The result showed that maxillary teeth with p<0.05 was detected at the second point-first intermolar. For mandibular, p<0.05 were detected on first interpremolar, second interpremolar, and first intermolar. Comparing mean value of the point of malocclusion-angle classification, it was showed that dental arch width of class I was narrower than class II, while class I and class II were wider than class III. Conclusion: There were differences of dental arch width on malocclusion Angle classification.